Histopathological Changes of Renal Tubules in Metformin and A. Crassna Leaf Extract treated STZ-induced Diabetic Rats - Khunchai, Sasiprapa; Jarernsook, Rattanaporn; Monthathong, Thanapoom; Chanasong, Rachanee; Chootip, Krongkarn; Ingkaninan, Kornkanok; Wongwad, Eakkaluk; Kanamnouy, Kitsaphon; Sudsaward, Sangkab (Naresuan University Journal: Science and Technology (NUJST); Vol 31 No 1 (2023): January - March 2023, 2022)
This research is part of the project to study and assess the anti-diabetes effects of A. Crassna leaf extract treatment for STZ-induced diabetic rats, to evaluate tissue damage amelioration. To determine the side effects of Diabetes Mellitus (DM)-treated rats, metformin (a common anti-hyperglycemic medicine) and A. Crassna crude extract were tested on kidney tissue from the diabetic rats. We evaluated the changes in renal tubular histology in the kidneys of the diabetic rats that were given metformin and A. Crassna crude extract. Paraffin blocks with kidney samples embedded were prepared for each group: 1) control group, 2) diabetic group, 3) metformin-treated diabetes group, 4) A. Crassna leaf extract-treated diabetes group by 300 ml/kg (K300), and 5) 1000 ml/kg (K1000). The tissue sections were stained with routine hematoxylin and eosin and a special staining technique for glycogen accumulation identification, periodic acid-Schiff (PAS) reagent, to identify tubular pathology. In hyperglycemic conditions, as shown in the DM model in the metformin-treated group, and K300 and K1000 A. Crassna -treated investigations, subnuclear vacuolizations (Armanni-Ebstein lesions) were discovered to have increased by approximately 19.09% ( p= 0.01) in metformin-treated diabetic rats. However, tubular lesions were also observed in the DM, K300, and K1000 groups. The distal tubule is often targeted for tubular anomalies that do not damage the juxtaglomerular structure. The study demonstrates the renal tubular toxicity of metformin and A. Crassna leaf extract in acute hyperglycemic rats, possibly providing a renal side effect for diabetic treatment. Keywords: A. Crassna , Diabetic nephropathy, Metformin, STZ-induced diabetic rats, PAS